PENGEMBANGAN MEDIA FLIPBOOK UNTUK MENINGKATKAN SIKAP TANGGUNG JAWAB DI SEKOLAH DASAR - Alfiyani Nurjannah; Lidya Novita Elisabeth Marpaung; Sarah Liviany Fazrin Harahap3; Arita Marini (Bajang Institute, 2023)
This research was motivated by students' inability to recognize the attitude of responsibility that is frequently seen in various cases of students at school, such as a student who cannot complete his assignments properly, cannot care for his own belongings, does not apologize when he makes mistakes, and some children do not want to clean up items or equipment that he has used and return them to where he originally took them. Efforts that can be made to overcome these problems include developing character education in the teaching and learning process, including teaching materials that contain character education material, and developing innovative, creative, effective, and fun learning media innovations. One of the learning media that can be developed is flipbook media. Teachers must be able to develop this technology-based media to increase the attitude of responsibility in students. This study aims to examine more deeply the role of flipbook media in increasing students' responsible attitudes in elementary schools. The method used is a qualitative one using descriptive analysis techniques and literature studies. In this research, there are several stages to describe the data using data collection through various sources such as research articles, books, and other literature relevant to this research..